Dynamical chaos rise in the system of large number of nonlinear coupled oscillators - Buts, V.A.; Kovalchuk, I.K.; Tarasov, D.V. (Вопросы атомной науки и техники, 2007)
The problem of dynamical chaos arising in distributed systems is considered. It was shown that in many cases it is possible to allocate relatively isolated subsystem which may be simpler for investigation. We suppose that chaos in this subsystem leads to chaotic behavior of all system. Besides, the allocated subsystem may be used for describing complex dynamics of nonlinear three-wave interaction, in particular, in plasma systems. The analytical criterion of arising dynamics chaos in distributed system was obtained. This criterion was confirmed by numerical simulation. Розглядається проблема виникнення динамічного хаосу в розподілених системах. Показано, що в багатьох випадках можливо виділити відносно ізольовані підсистеми в розподілених системах, які можуть бути значно простіше для дослідження. Ми вважаємо, що хаос у цих підсистемах є джерелом хаотичної поведінки всієї системи. Крім того, виділені системи можуть бути використані, для опису складної динаміки нелінійної трьох-хвильової взаємодії, зокрема в плазмових системах. Отримано аналітичний критерій виникнення динамічного хаосу для виділених підсистем. Цей критерій підтверджений чисельними дослідженнями. Рассматривается проблема возникновения динамического хаоса в распределенных системах. Показано, что во многих случаях возможно выделить относительно изолированные подсистемы в распределенных системах, которые могут быть значительно проще для исследования. Мы полагаем, что хаос в этих подсистемах является источником хаотического поведения всей системы. Кроме того, выделенные системы могут быть использованы для описания сложной динамики нелинейного трехволнового взаимодействия, в частности, в плазменных системах. Получен аналитический критерий возникновения динамического хаоса для выделенных подсистем. Этот критерий подтвержден численными исследованиями.